THE DETERMINANTS OF ACCESS TO ADOLESCENT- FRIENDLY HEALTH SERVICE: A CASE CONTROL STUDY - Izzatul Arifah; Lenni Ayu Kusumawardani; Dwi Hendriyaningsih; Mukti Aji Wibisono; Estu Puji Lestari (Universitas Airlangga, 2020)
Background: Adolescents need to access Adolescent-Friendly Health Service (AFHS) to get it’s benefit in order to improve adolescent health. However, the current adolescent access to that service remains low with the access prevalence under 50%).Aim: This study determined factors that affected adolescents’ access to AFHS.Methods: This school-based case control study was conducted in 9 junior and senior high schools in the area of Sangkrah and Kratonan in Surakarta District. There were 162 cases (who accessed the AFHS by guidance from health professionals and peer educators) and 162 controls (those who did not) who were chosen using total sampling and proportionate random sampling technique, respectively. A multiple logistic regression analysis was used to assess the determinant factors of AFHS access.Results: Access to AFHS was significantly determined by knowledge of the program and perceived demand. A probability of finding adolescents who had knowledge of the program was 6 times higher in the case group than in control group with the OR value of 6.1 (95% CI 3.3-11.1).Conclusion: Overall, the low adolescents’ access was mostly caused because of insufficient knowledge. Broadening information about the program and adolescents’ access to the program through electronic media and peer educators is required. Keywords: access, adolescent, Adolescent-Friendly Health service, AFHS.